Energy resources : utilization and technologies - Anjaneyulu, Yerramilli; Tuluri, Francis (Hyderabad : BS Publications, 2012)
This textbook examines the fundamentals of energy and current energy resources, technology developments, solutions to energy issues and new concepts.
Includes bibliographical references and index.
Keywords: Power resources; Energy development